Beautiful darkness - Vehlmann, Fabien 1972-; Pommepuy, Marie 1978-; Kerascoet; Dascher, Helge 1965- ([Montreal, Quebec] Drawn & Quarterly, 2014)
"Kerascoët's and Fabien Vehlmann's unsettling and gorgeous anti-fairy tale is a searing condemnation of our vast capacity for evil writ tiny. Join princess Aurora and her friends as they journey to civilization's heart of darkness in a bleak allegory about surviving the human experience. The sweet faces and bright leaves of Kerascoët's delicate watercolors serve to highlight the evil that dwells beneath Vehlmann's story as pettiness, greed, and jealousy take over. Beautiful Darkness is a harrowing look behind the routine politeness and meaningless kindness of civilized society." -- Provided by publisher
Keywords: Fairy tales -- Comic books, strips, etc; Princesses -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Comic books, strips, etc. -- France -- Translations into English